1999
DOI: 10.1016/s0304-3959(98)00268-1
|View full text |Cite
|
Sign up to set email alerts
|

Cost-of-illness of neck pain in The Netherlands in 1996

Abstract: The prevalence of neck pain in the general population ranges from 10 to 15%. The complaints can result in substantial medical consumption, absenteeism from work and disability. In this study we investigated the costs of neck pain in the Netherlands in 1996 to assess the financial burden to society. The study was based on prevalence data. Data sources included national registries, reports of research institutes and health care authorities. Direct health care costs were estimated for hospital care, general pract… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
211
0
11

Year Published

2003
2003
2017
2017

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 408 publications
(232 citation statements)
references
References 14 publications
2
211
0
11
Order By: Relevance
“…Then, a single and previously trained examiner assessed participants for investigating multidimensional aspects related to neck pain through Br-MPQ (14,15), and neck pain related disability by NDI (17). recurrent episodes of pain, personal suffering and loss of productivity at work (5,8).…”
Section: Instruments and Outcomesmentioning
confidence: 99%
“…Then, a single and previously trained examiner assessed participants for investigating multidimensional aspects related to neck pain through Br-MPQ (14,15), and neck pain related disability by NDI (17). recurrent episodes of pain, personal suffering and loss of productivity at work (5,8).…”
Section: Instruments and Outcomesmentioning
confidence: 99%
“…Prevalence of neck pain is even higher in office workers than in the general community, reaching levels as high as 50 to 60% [2,6,8,19]. Neck pain can impact on the ability to perform normal daily activities, and the resultant treatment costs and work loss contribute to a substantial economic burden for both the individual and society [1,4,5]. Data about the incidence of neck pain in office workers are lacking, as previous studies have reported on estimates of prevalence.…”
Section: Introductionmentioning
confidence: 99%
“…[1] The severity of neck pain and the related disability can affect daily social and functional activities, which may even involve emotional and psychological aspects. [5][6][7][8][9][10][11] Thanks to the approval of the International ClassiĂž cation of Functioning, Disability and Health (ICF) by the World Health Assembly in 2001, neck pain and related consequences could be clearly understood and evaluated by a universal conceptual model termed as 'biopsychosocial health,' which integrated the biomedical and societal models of functioning and disability. [12] Hence, the outcome measures for any disease that predict the disease progress and response should carefully consider the biopsychosocial model involved in the evaluation of the disease process.…”
Section: Introductionmentioning
confidence: 99%